Lo sviluppo sostenibile come sfida per le città del XXI secolo: insegnamenti tratti dall’esperienza di Freiburg im Breisgau - Mazzette, Antonietta; Spanu, Sara (Scienze del Territorio, 2015)
By 2050, 70% of the world population will live in urban areas. Which features should the 21st century cities have in order to guarantee a good quality of life for their inhabitants in terms of ma-terial and cultural prosperity, and social cohesion? The answer lies within the indicators used by the European commission in determining the ranking of Green cities: eco-friendly mobility, increase of green areas, reduction of soil consumption, and the involvement of citizens in the urban policymaking processes, just to name a few. This paper presents some notes on urban environmental and social sustainability, which is an open and controversial issue. In the first part, the focus is on three main reasons - territorial, social and political reasons - that should lead us to promote sustainable policies. In the second part, we will present the case study of the German city of Freiburg, widely recognized for its achievements in relation to the environmental sustainability policies adopted, but with some crucial aspects to be explored in terms of social sustainability and citizen participation.